Mechanistic insight into the RNA-stimulated ATPase activity of tick-borne encephalitis virus helicase - Anindita, Paulina Duhita; Halbeisen, Marco; Řeha, David; Tuma, Roman; Franta, Zdenek (The Journal of biological chemistry, 2022)
The helicase domain of nonstructural protein 3 (NS3H) unwinds the double-stranded RNA replication intermediate in an ATP-dependent manner during the flavivirus life cycle. While the ATP hydrolysis mechanism of Dengue and Zika viruses NS3H has been extensively studied, little is known in the case of the tick-borne encephalitis virus NS3H. We demonstrate that ssRNA binds with nanomolar affinity to NS3H and strongly stimulates the ATP hydrolysis cycle, whereas ssDNA binds only weakly and inhibits ATPase activity in a noncompetitive manner. Thus, NS3H is an RNA-specific helicase, whereas DNA might act as an allosteric inhibitor. Using modeling, we explored plausible allosteric mechanisms by which ssDNA inhibits the ATPase via nonspecific binding in the vicinity of the active site and ATP repositioning. We captured several structural snapshots of key ATP hydrolysis stages using X-ray crystallography. One intermediate, in which the inorganic phosphate and ADP remained trapped inside the ATPase site after hydrolysis, suggests that inorganic phosphate release is the rate-limiting step. Using structure-guided modeling and molecular dynamics simulation, we identified putative RNA-binding residues and observed that the opening and closing of the ATP-binding site modulates RNA affinity. Site-directed mutagenesis of the conserved RNA-binding residues revealed that the allosteric activation of ATPase activity is primarily communicated via an arginine residue in domain 1. In summary, we characterized conformational changes associated with modulating RNA affinity and mapped allosteric communication between RNA-binding groove and ATPase site of tick-borne encephalitis virus helicase.
Keywords: DNA, Single-Stranded; RNA-helikasy; flavivirus; RNA, Double-Stranded; RNA helicase; dvouvláknová RNA; virové nestrukturální proteiny; Viral Nonstructural Proteins; nonstructural protein 3; lidé; adenosintrifosfatasy; adenosintrifosfát; viry klíšťové encefalitidy; crystal structure; Encephalitis Viruses, Tick-Borne; Phosphates; Adenosine Triphosphate; viral protein; RNA Helicases; enzyme kinetics; tick-borne encephalitis virus; ATPase; molecular dynamics; Adenosine Triphosphatases; jednovláknová DNA; fosfáty; Humans